Jenis Phytotelmata Sebagai Tempat Perindukan Alami Nyamuk Aedes sp. Berdasarkan Jumlah Telur yang Mendiaminya di Area Kampus Universitas Lampung - Ramadhanti, Saskya Adrila; Rosa, Emantis; Rustiati, Elly Lestari (Bioma : Berkala Ilmiah Biologi, 2020)
Phytotelmata is the part of a plant that can collect water and can be used as a natural breeding site for insects including mosquitoes. This research was conducted in August-December 2019 in the University of Lampung to find out the species of phytotelmata that have the potential to be Aedes sp. breeding site based on the number of eggs that inhabit it, as one of the efforts to controlling Dengue Hemorrhagic Fever vector. The study used experimental methods with complete random design. Analysis data was done using ANOVA and continued with the BNT test with 95% (Î±=5%) confidence. This research show that it found six species of Phytotelmata in the University of Lampung, such as Cocos nucifera, Artocarpus heterophyllus, Bambusa sp., Bauhinia purpurea, Colocasia esculenta, and Musa paradisiaca. The most potential species of phytotelmata became the natural breeding site for Aedes sp. mosquito is a Cocos nucifera with an average of 16,33 eggs.